Jewish childhood in Kraków: a microhistory of the Holocaust - Sliwa, Joanna (Rutgers University Press, 2021)
Chapter 1: Navigating shifts in German-occupied Kraków -- Chapter 2: Adapting to life inside the ghetto -- Chapter 3: Clandestine activities by and on behalf of children -- Chapter 4: Child welfare: continuity and change -- Chapter 5: Concealed presence in the camp -- Chapter 6: Survival through hiding and flight.